2021
DOI: 10.1002/app.51322
|View full text |Cite
|
Sign up to set email alerts
|

Solution blow spinning of piezoelectric nanofiber mat for detecting mechanical and acoustic signals

Abstract: Solution blow spinning (SBS) technique can produce nanofibers (NFs) mat in large‐scale production. In this work, the SBS was used to fabricate piezoelectric polyvinylidene fluoride (PVDF) NF membranes that can be utilized for energy harvesting applications. The effect of operating air pressure from (2–5 bar) on the surface morphology of the NFs has been studied. The structural analysis for crystalline polymorph β‐phase for PVDF powder, casted film, electrospinning and SBS NFs has also been presented with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Electrospinning has been the most promising as it can form nanofibers from solutions or melts with variable diameters. Additionally, it has been reported that the β-phase content in PVDF nanofibers produced by electrospinning is higher than that of PVDF cast films, thereby improving its piezoelectric properties 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning has been the most promising as it can form nanofibers from solutions or melts with variable diameters. Additionally, it has been reported that the β-phase content in PVDF nanofibers produced by electrospinning is higher than that of PVDF cast films, thereby improving its piezoelectric properties 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibers possessing “smart” properties are becoming tremendously important due to their potential applications, such as in displays and wearable electronic textiles 8 . Solution blowing was also utilized to form PVDF nanofiber mats, which hold great promise as piezoelectric sensors for various energy‐harvesting technologies, as well as for acoustic sensors 9 . The present group formed fiber‐reinforced self‐healing polymer matrix composites (PMC) embedded with electrospun or solution‐blown nanofibers 5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Solution blowing was also utilized to form PVDF nanofiber mats, which hold great promise as piezoelectric sensors for various energy-harvesting technologies, as well as for acoustic sensors. 9 The present group formed fiber-reinforced self-healing polymer matrix composites (PMC) embedded with electrospun or solution-blown nanofibers. 5,10 Polymer adhesion and sintering in compound nonwovens were studied by Staszel et al 11 aiming for solution-blown nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Scalable methods for fabricating such materials include but are not limited to electrospinning and solution blow spinning (SBS) 2 . The unique properties of nano‐ and submicron fibrous materials, like the high specific surface area, high porosity, good mechanical properties, and structural characteristics associated with their size, make them candidates as building materials for various products, including smart materials, through energy and catalysis applications, materials for environmental protection to biomedical applications 3–13 …”
Section: Introductionmentioning
confidence: 99%
“…2 The unique properties of nano-and submicron fibrous materials, like the high specific surface area, high porosity, good mechanical properties, and structural characteristics associated with their size, make them candidates as building materials for various products, including smart materials, through energy and catalysis applications, materials for environmental protection to biomedical applications. [3][4][5][6][7][8][9][10][11][12][13] The spinning of polymer solutions to the fibrous materials requires an interplay between specific solution properties and processing parameters regardless of the applied technique. 14 Determining the values of the processing parameters and the determination of polymer solution properties remains a significant challenge, especially in new processes like the SBS.…”
Section: Introductionmentioning
confidence: 99%